Treatment of Triple Negative Cell Lines with Olaparib to Block DNA Repair - Pinheiro, Marina Gobbe Moschetta; Colombo, Jucimara; Tuckumantel, Murillo de Souza; Rebolho, Gabriela Karam; Zuccari, Debora Aparecida Pires de Campos [UNESP] (Bentham Science Publishers, 2022)
Background: The most aggressive breast cancer is the triple negative histological type, and the gold standard for its treatment is platinum salts, such as carboplatin. Due to high recurrence, there is a need to test new drugs, such as PARP inhibitors (PARPi), that induce lethality in cells with DNA damage. Olaparib is a PARPi, already used in some tumors but not tested in canine species. Thus, the aim of this study was to demonstrate the efficacy of olaparib in inhibiting DNA repair and control disease progression by decreasing the migration capacity of mammary tumor cells. Methods: The cell lines CF41.Mg and MDA-MB-468 were cultured and MTT was performed to define the best dose of carboplatin. Next, the cells were treated with 10 µM carboplatin, olaparib, and with a combination of both for 24 hours. PARP-1 protein and gene expression were evaluated by immunofluorescence, western blotting, and qRT-PCR, respectively. The analysis of cell migration was performed in transwell chambers. Results: For CF41.Mg and MDA-MB-468 cell lines, there was a decrease in PARP-1 protein and gene expression after treatment with carboplatin, olaparib, and both in combination compared to the group without treatment (control) (p<0.05). Moreover, in both lines, a reduction in invasion rate was observed after treatment with carboplatin, olaparib and when combined, compared to the control group (p<0.05). Conclusion: Our data suggest that carboplatin and olaparib were able to block DNA repair and control the cancer invasion, especially when used in combination. The results with olaparib in the canine line are unpublished. The olaparib should be a possible agent against human breast cancer and canine mammary tumors.
Keywords: Carboplatin; DNA; mammary tumors; olaparib; PARP-1; triple negative cell lines